"Empowered patient" or "doctor knows best"? Political economy analysis and ownership. Issue 1 (2nd January 2016) - Fisher, Jonathan; Marquette, Heather
ABSTRACT: Efforts to incorporate "political thinking" into policy-making and practice in OECD-DAC development agencies have increasingly focused on the use of "political economy analysis" (PEA) frameworks and tools. While recognising the fundamental value of promoting politically informed programming, this article nevertheless highlights how contemporary efforts to this end have largely ignored another central development agenda: the ownership paradigm. Emphasising the highly donor-centric nature of PEA design and methodology, we explore critiques and justifications of this state of affairs, ultimately arguing that donors would benefit from embracing a more flexible and context-specific understanding of ownership.